2017
DOI: 10.1001/jamasurg.2016.4619
|View full text |Cite
|
Sign up to set email alerts
|

Complementing Operating Room Teaching With Video-Based Coaching

Abstract: Video-based coaching is a novel and feasible modality for supplementing intraoperative learning. Objective evaluation demonstrates that video-based coaching may be particularly useful for teaching higher-level concepts, such as decision making, and for individualizing instruction and feedback to each resident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 43 publications
0
92
2
1
Order By: Relevance
“…Several investigations of the impact of coaching in surgical education have yielded promising results, with coaching interventions demonstrating improvements in both technical and non-technical skills. [8][9][10][11] Lovell's recent review of coaching in medical education revealed good quality data showing that coaching improves technical skills acquisition, reduces surgical error, improves examination scores and identifies struggling students. 2 But as published work explores what coaching does, it has not tended to illuminate what coaching is in medical education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations of the impact of coaching in surgical education have yielded promising results, with coaching interventions demonstrating improvements in both technical and non-technical skills. [8][9][10][11] Lovell's recent review of coaching in medical education revealed good quality data showing that coaching improves technical skills acquisition, reduces surgical error, improves examination scores and identifies struggling students. 2 But as published work explores what coaching does, it has not tended to illuminate what coaching is in medical education.…”
Section: Resultsmentioning
confidence: 99%
“…A growing literature suggests that coaching approaches may be valuable in certain domains of medical education. Several investigations of the impact of coaching in surgical education have yielded promising results, with coaching interventions demonstrating improvements in both technical and non‐technical skills . Lovell's recent review of coaching in medical education revealed good quality data showing that coaching improves technical skills acquisition, reduces surgical error, improves examination scores and identifies struggling students .…”
Section: Introductionmentioning
confidence: 99%
“…An official informed consent stating the purpose of the data recordings, where the data recordings are analysed, what the expected benefits for the participants are, and how the data are stored securely may help in gaining support and momentum for the MDR initiative. It should be emphasized that their safety and personal privacy is protected, ensuring full transparency of the methods used. Based on this review and the authors' experience, an overview of the recommended practice and legal guidelines is presented in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Application of video recording during surgery is a new and applicable method, which can complement training in the operating room (14). The findings show that application of this method is very suitable for teaching high levels of cognition such as clinical decision-making, individual training, and feedback.…”
Section: Video-based Trainingmentioning
confidence: 97%
“…The findings show that application of this method is very suitable for teaching high levels of cognition such as clinical decision-making, individual training, and feedback. Both residents and teachers claim that this training method is useful for training in the operating room; in addition to increasing educational opportunities, it reduces the pressure of teaching in the operat-ing room (14). Video-based learning has many advantages including increased concentration on learning, creating valuable learning opportunities, providing feedback, and facilitating cognitive thinking (14).…”
Section: Video-based Trainingmentioning
confidence: 99%